Halp Score: A Simple and Easily Accessible Index for Predicting Prognosis in Colorectal Cancer Patients - Zeynep Güç (Genel Tıp Dergisi)
Objective: Colorectal cancer is the fourth most common malignant tumor in the world, and survival times are seen to increase together with the increase in the options for targeted therapies, local ablative applications, and supportive care. The Hemoglobin, Albumin, Lymphocyte and Platelet (HALP) score is used as a prognostic factor in different types of cancers. The aim of this study was to analyze the prognostic value of the HALP score in patients diagnosed with de novo metastatic colorectal cancer. Methods: De novo mCRC patients who were followed-up in the period from January 2017 to December 2021, were retrospectively evaluated. The optimal cut-off point for the HALP score was calculated with the Receiver Operating Characteristic (ROC) curve analysis. Predictive factors for overall survival were assessed with univariate analysis. Survival times were assessed with the Kaplan-Meier analysis. Results: A total of 213 patients were included in the study. Univariate analysis showed that patients with low BMI, high ECOG score, and tumors located in the right colon, and RAS mutant patients, and those with a low HALP score were associated with worse survival rates. Namely, the overall survival time of patients with a HALP score >16.74 was found as 91 months, while the overall survival time of patients with a HALP score ≤16.74 was found as 16 months (p<0.001). Conclusion: Our study showed the HALP score to be a simple, cost-effective, and useful marker that can predict OS in mCRC patients.